User perception of Bitcoin usability and security across novice users. Issue 126 (June 2019) - Alshamsi, Abdulla; Andras, Prof. Peter
Highlights: Users perceived the usability of credit/debit cards higher than Bitcoin. Low user usability perception of Bitcoin has a negative influence on users' security perceptions of Bitcoin. Insufficient government regulation and Bitcoin application standards are among many reasons that affect users' usability and security perceptions of Bitcoin as a payment system. Need for further investigation to get a better understanding of users and address user usability and security issues and the trade-off between these. Abstract: This paper investigates users' perceptions and experiences of an anonymous digital payment system (Bitcoin) and its influence on users in terms of usability and security in comparison to other non-anonymous payment systems such as credit/debit cards. This paper identifies users' perceptual differences in terms of usability and security. Two versions of user survey are used to collect data, which reveal significant differences in users' perceptions of credit/debit cards and Bitcoin. The usability attributes of both systems examined show that respondents perceive the usability of credit/debit cards to be higher than Bitcoin. This has a great negative influence on users' security perceptions of Bitcoin. We conclude that Bitcoin, as a crypto-currency, is still in its infancy and requires user education and a new way of thinking. The study recommends developing users' mental models to deepen developers' understanding of anonymous digital payment technology and improve user-centred design. We also make recommendations with respect to e-government services that may be developed relying on crypto-currencies.